Dampak Otonomi Khusus Pada Ekonomi Orang Asli Papua Setelah Implementasi Kebijakan Pemerintahan - Salmawati, Salmawati; Purnomo, Arie; Nikmatul Ula, Siti Nurul; Rais, Lukman; Ikhwan, Saiful (Universitas Muhammadiyah Sorong, 2024)
The economy of indigenous Papuans is still relatively low even though special autonomy funds continue to be given to regional governments every year. The aim of the research is to determine the impact of special autonomy on the economy of indigenous Papuans after implementing the policy in Sorong City, Southwest Papua. This research uses qualitative research methods with a descriptive approach. Qualitative methodology presents a research strategy that presents descriptive data in the form of written and verbal messages from the subjects and their observed attitudes. The results of the research show that the implementation of the Special Autonomy policy in Papua still has significant challenges. Communication factors, resources, disposition and bureaucratic structure have an important role in the success of policy implementation. There is an urgent need to improve coordination between the central and regional governments, as well as involving all elements of society, especially those below the poverty line, in the policy process. The conclusion of this research is an increase in the implementation of the Special Autonomy policy to ensure the development and welfare of the Papuan people. Strategic steps need to be taken to optimize Papua's natural and human resources, as well as improve economic and social conditions in the area. Thus, this research makes a valuable contribution to understanding and dealing with existing problems more effectively.